(3GdEbfGY aj Md CdaGX CHj TLGYs - (3GdTQHjfj GdeUQj GdTGaYj, TeS GdOjf (B- (3GdNWjH, eMeO Hf CMeO, J (B977 (3g`s ((3YHO GdXGgQ Hf eMeO GdTjJjs)
(3ChdgG (B:s
(3Chd eG ajg bhdg (B( (3GdeZjQI cGf jCPN EfGAjf aj hGMO bdJGf haj GdBNQ OhfgeG (B) (3ef cJGH GdWgGQIs
(3BNQgG (B:s
(3HNdGa eG dh CJda eWQRG aEfg jdReg bjeJg hdG jdReg CLQI GdJWQjR HOd bjeI GdKhH ZGdHG hdG cPdc GdcJGHI aEfgG bO JfbUgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 6s
(3eYLe GdeDdajf (B3 / 69s
(3EjVGM Gdecfhf (B2 / 448s
(3TPQGJ GdPgH (B8 / 384s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs